Application for Control and Monitoring of Grow Beds Using IoT - Paez-Quinde, David (2023)
Automation, in general, facilitates thecontrol of different types of processes; its result allows high-qualityproducts. The development of this research is based on the effect ofglobalization, which has led farmers to opt for IoT and automation in the plantedarea. This work presents a control and monitoring system using a mobileapplication developed in App inventor that allows visualizing the data fromanywhere. The data obtained are the environmental temperature and the humidityof the soil, and the irrigation is controlled through a pump. The system isbased on an ESP32 board and the ThingSpeak platform. The programmingincorporates two control modes, manual and automatic; in the second case, acontrol with hysteresis is activated to maintain a range of humidity in thegrow bed. The results show measurements of the variables and the scores of anevaluation carried out by the user that allows validation of this proposal.